1996
DOI: 10.1159/000189108
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 72/73 in Normal and Diseased Kidneys

Abstract: The induction of heat shock (stress) proteins (HSP) is a response by cells due to a variety of physical, chemical, and infectious agents. They have a significant role as cytoprotectants, in the regulation of cellular functions, and in the recovery after sublethal injury. Using antibody to mammalian HSP 72/73, we have performed an immunohistological study of human renal tissue in normal and diseased states, including idiopathic nephrotic syndrome, proliferative and crescentic glomerulonephritis, and interstitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Increased HSP expression is found in patients with various forms of nephritis including minimal change glomerulonephritis, FSGS, membranous nephropathy, and acute interstitial nephritis in the loci of acute interstitial infiltration (Venkataseshan and Marquet 1996). Marzec et al (2009) revealed the decreased HSP72 expression on the surface of peripheral blood monocytes of patients with CKD as compared with the control.…”
Section: Role Of Hsp70 and Hsp60 In The T Cell Regulation Of Chronic mentioning
confidence: 95%
See 1 more Smart Citation
“…Increased HSP expression is found in patients with various forms of nephritis including minimal change glomerulonephritis, FSGS, membranous nephropathy, and acute interstitial nephritis in the loci of acute interstitial infiltration (Venkataseshan and Marquet 1996). Marzec et al (2009) revealed the decreased HSP72 expression on the surface of peripheral blood monocytes of patients with CKD as compared with the control.…”
Section: Role Of Hsp70 and Hsp60 In The T Cell Regulation Of Chronic mentioning
confidence: 95%
“…In kidneys with the puromycin aminonucleoside induced nephrosis, HSP73 accumulates in the cytoplasm at a level higher than in the nucleus in association with the severity of renal dysfunction and proteinuria (Komatsuda et al 1992). Somewhat different localization of HSP70 expression in normal human kidney was demonstrated by Venkataseshan and Marquet (1996) and Dinda et al (1998). HSP73/72 showed a uniform fine granular cytoplasmic staining of visceral glomerular epithelial cells and epithelia of distal convoluted tubules and collecting ducts without localization in proximal tubules.…”
Section: Hsp73 In Normal Renal Tissuementioning
confidence: 99%
“…Recent studies suggested that HSP 72/73 expression of renal tubular epithelial cells may be induced not only by focal inflammatory alterations of the cellular environment but also by systemic influences, such as hemodialysis [44, 45]. Particularly during CAPD, repeated exposure to dialysis solutions probably also modulate mesothelial HSP expression.…”
Section: Discussionmentioning
confidence: 99%
“…A number of published reports show that HSPs can be elevated in kidneys in vivo, particularly as a result of disease or injury [9, 10, 11, 12, 13]. However, deficient cytoprotection by HSP70 [7] or low HSP levels in kidney relative to other organs [8, 14] could explain the marked sensitivity of RPT cells to various modes of injury.…”
Section: Discussionmentioning
confidence: 99%
“…This stress response is tissue-dependent and may be attenuated, or absent, in some cell types that exhibit a high sensitivity to a variety of stress conditions [3, 4, 5, 6]. In particular, susceptibility of renal proximal tubule (RPT) cells to various toxic agents could be related to a limited capacity for mounting a cellular stress response [7, 8], although the expression of certain HSPs is elevated in numerous renal disease states [9, 10, 11, 12, 13]. Constitutive HSP levels in kidney, however, may be quite low and with the possible exception of HSP70 may be significantly lower than those in liver, for example [14].…”
Section: Introductionmentioning
confidence: 99%